2010
DOI: 10.1111/j.1540-4560.2010.01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Support Groups, Stigma, and Self-Esteem: Positive and Negative Implications of Group Identification

Abstract: Research into the relationship between stigmatization and well-being suggests that identification with a stigmatized group can buffer individuals from the adverse effects of stigma. In part, this is because social identification is hypothesized to provide a basis for social support which increases resistance to stigma and rejection of negative in-group stereotypes. The present research tests this model among individuals with mental health problems. As hypothesized, group identification predicted increased soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
204
3
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(225 citation statements)
references
References 39 publications
16
204
3
2
Order By: Relevance
“…On the other hand, being part of a social group can have a positive impact on health-related behaviours (Crabtree, Haslam, Postmes, & Haslam, 2010;Jetten, Haslam, Haslan, Dingle, & Jones, 2014). For example, the presence of varied types of social support (friend, family, support groups) appear to aid in the alcohol recovery process by promoting sustained abstinence within alcohol anonymous groups (for review see, Groh, Jason, & Keys, 2008).…”
Section: Social Drinkingmentioning
confidence: 99%
“…On the other hand, being part of a social group can have a positive impact on health-related behaviours (Crabtree, Haslam, Postmes, & Haslam, 2010;Jetten, Haslam, Haslan, Dingle, & Jones, 2014). For example, the presence of varied types of social support (friend, family, support groups) appear to aid in the alcohol recovery process by promoting sustained abstinence within alcohol anonymous groups (for review see, Groh, Jason, & Keys, 2008).…”
Section: Social Drinkingmentioning
confidence: 99%
“…Very little research has found evidence of this to date, however, one recent study found that people in treatment for substance use disorder had better outcomes to the extent that they disidentified with previous substance using identities (Dingle et al 2014). One particularly relevant study (Crabtree et al 2010) explored social identification with mental health support groups and the consequences for social support, stigma-resistance and self-esteem. Interestingly, while social identification was associated with greater perceived support and stigma resistance, this had the effect of suppressing an otherwise negative relationship between identification and self-esteem.…”
mentioning
confidence: 99%
“…Interestingly, Crabtree et al (2010) found evidence in support of both the amplification hypothesis and the buffering hypothesis. These researchers investigated members of mental health support groups in order to determine whether identifying with these stigmatized groups had positive or negative outcomes on psychological well-being.…”
Section: Contrasting the Amplification And Buffering Predictionsmentioning
confidence: 52%
“…On the one hand, stronger social class identification may amplify the observed association between social class and mental health because identification strengthens the relation between the social status of the social class group and group members' self-definition (Crabtree et al, 2010;Ellemers et al, 1999;Martiny & Rubin, 2016;McCoy & Major, 2003;Rubin & Hewstone, 1998, 2004. On the other hand, stronger social class identification may weaken the observed association between social class and mental health because it is associated with a sense of belonging and connectedness that buffers the negative effects of membership in low social class groups (Crabtree et al, 2010;Cruwys et al, 2014;Elliott & Doane, 2015;Greenaway et al, 2016;Jetten et al, 2012;Kawachi & Berkman, 2001;Sani et al, 2012).…”
Section: Contrasting the Amplification And Buffering Predictionsmentioning
confidence: 99%